Ceramic Ecology: an Approach to the Study of Early Cultures of the Near East - Matson, F. R.
symposium on "Ceramics and Man" held at Burg Wartenstein in Austria from September 2-12, 1961; zitiert RA 58 (1964) 8 n. 1.